3β-Isoobeticholic acid efficiently activates the farnesoid X receptor (FXR) due to its epimerization to 3α-epimer by hepatic metabolism. Issue 202 (September 2020) - Stefela, Alzbeta; Kaspar, Miroslav; Drastik, Martin; Holas, Ondrej; Hroch, Milos; Smutny, Tomas; Skoda, Josef; Hutníková, Miriama; Pandey, Amit V.; Micuda, Stanislav; Kudova, Eva; Pavek, Petr
Graphical abstract: Highlights: 3β-IsoOCA is an efficient FXR activator due to epimerization to OCA in the hepatic cells. 3, 7-DehydroOCA is a novel potent GPBAR1 ligand. Oxidation or epimerization on C3/C7 positions in the OCA scaffold abrogate affinity to FXR or GPBAR1. 6-Ethylidene in the OCA scaffold abrogates affinity to FXR and GPBAR1. Abstract: Bile acids (BAs) are important signaling molecules acting via the farnesoid X nuclear receptor (FXR) and the membrane G protein-coupled bile acid receptor 1 (GPBAR1). Besides deconjugation of BAs, the oxidoreductive enzymes of colonic bacteria and hepatocytes enable the conversion of BAs into their epimers or dehydrogenated forms. Obeticholic acid (OCA) is the first-in-class BA-derived FXR agonist approved for the treatment of primary biliary cholangitis. Herein, a library of OCA derivatives, including 7-keto, 6-ethylidene derivatives and 3β-epimers, was synthetized and investigated in terms of interactions with FXR and GPBAR1 in transaction assays and evaluated for FXR target genes expression in human hepatocytes and C57BL/6 mice. The derivatives were further subjected to cell-free analysis employing in silico molecular docking and a TR-FRET assay. The conversion of the 3βhydroxy epimer and its pharmacokinetics in mice were studied using LC–MS. We found that only the 3β-hydroxy epimer of OCA (3β-isoOCA) possesses significant activity to FXR in hepatic cells and mice. However, in a cell-free assay, 3β-isoOCA had about 9-times lower affinity to FXR than did OCA. We observed that 3β-isoOCA readily epimerizes to OCA in hepatocytes and murine liver. This conversion was significantly inhibited by the hydroxy-Δ 5 -steroid dehydrogenase inhibitor trilostane. In addition, we found that 3, 7-dehydroobeticholic acid is a potent GPBAR1 agonist. We conclude that 3β-isoOCA significantly activates FXR due to its epimerization to the more active OCA by hepatic metabolism. Other modifications as well as epimerization on the C3/C7 positions and the introduction of 6-ethylidene in the CDCA scaffold abrogate FXR agonism and alleviate GPBAR1 activation.